Evidence-based Sterility: The Evolving Role of Field Sterility in Skin and Minor Hand Surgery. Issue 11 (November 2019) - Yu, Janelle; Ji, Tianshu Angela; Craig, Michael; McKee, Daniel; Lalonde, Donald H.
Abstract : Summary: Field sterility is commonly used for skin and minor hand surgery performed in the ambulatory setting. Surgical site infection (SSI) rates are similar for these same procedures when performed in the main operating room (OR). In this paper, we aim to look at both current evidence and common sense logic supporting the use of some of the techniques and apparel designed to prevent SSI. This is a literature review of the evidence behind the ability of gloves, masks, gowns, drapes, head covers, footwear, and ventilation systems to prevent SSIs. We used MEDLINE, EMBASE, and PubMed and included literature from the inception of each database up to March 2019. We could not find substantial evidence to support the use of main OR sterility practices such as head covers, gowns, full patient draping, laminar airflow, and footwear to reduce SSIs in skin and minor hand surgery. Field sterility in ambulatory minor procedure rooms outside the main OR is appropriate for most skin and minor hand surgery procedures. SSIs in these procedures are easily treatable with minimal patient morbidity and do not justify the cost and waste associated with the use of main OR sterility.